Exclusion of the alpha 1(II) collagen structural gene as the mutant locus in type II Ehlers-Danlos syndrome. Issue 7 (July 1985) - Wordsworth, P; Ogilvie, D; Smith, R; Sykes, B
Abstract : We have used a high frequency site polymorphism within the human pro-alpha 1(II) collagen gene (COL2A1) in order to examine the segregation of this gene within a large pedigree with type II Ehlers-Danlos syndrome (EDS). The EDS gene and the collagen gene segregate independently within the pedigree and therefore COL2A1 can be excluded as the mutant locus.